Identification of 58 Mutations (26 Novel) in 94 of 109 Symptomatic Spanish Probands with Protein C Deficiency - Martos, Laura; Fernández-Pardo, Álvaro; López-Fernández, María F.; Ibáñez, Francisco; Herrero, Sonia; Tàssies, Dolors; González-Porras, José R.; Solmoirago, María J.; Costa, María J.; Reverter, Juan C.; Marco, Pascual; Roldán, Vanessa; Lecumberri, Ramón; Velasco, Francisco; Oto, Julia; Iruin, Gemma; Alonso, María N.; Vayá, Amparo; Bonanad, Santiago; Ferrando, Fernando; Martí, Edelmira; Cid, Ana R.; Plana, Emma; Oña, Francisca; Cuesta, Isabel; González-López, Tomás J.; España, Francisco; Medina, Pilar; Navarro, Silvia; on behalf of the Working Group of the Spanish Society of Thrombosis Haemostasis (SETH) (Thrombosis and Haemostasis, 2019)
Presently, no data on the molecular basis of hereditary protein C (PC) deficiency in Spain is available. We analyzed the PC gene (PROC) in 109 patients with symptomatic PC deficiency and in 342 relatives by sequencing the 9 PROC exons and their flanking intron regions. In 93 probands, we found 58 different mutations (26 novel). Thirty-seven consisted of a nucleotide change, mainly missense mutations, 1 was a 6-nucleotide insertion causing the duplication of 2 amino acids, and 4 were deletions of 1, 3, 4, and 16 nucleotides. Nine mutations caused type II deficiencies, with the presence of normal antigen levels but reduced anticoagulant activity. Using a PC level of 70% as lowest normal limit, we found no mutations in 16 probands and 25 relatives with PC levels ≤ 70%. On the contrary, 4 probands and 12 relatives with PC levels > 70% carried the mutation identified in the proband. The spectrum of recurrent mutations in Spain is different from that found in the Netherlands, where the most frequent mutations were p.Gln174* and p.Arg272Cys, and is more similar to that found in France, where the most frequent were p.Arg220Gln and p.Pro210Leu. In our study, p.Val339Met (9 families), p.Tyr166Cys (7), p.Arg220Gln (6), and p.Glu58Lys (5) were the most prevalent. This study confirms the considerable heterogeneity of the genetic abnormality in PC deficiencies, and allowed genetic counseling to those individuals whose PC levels were close to the lower limit of the normal reference range.
Keywords: protein C deficiency; gene mutations; venous thromboembolism; family study